The Impact and Mechanism of Action of Peptostreptococcus anaerobius on Chemotherapy Resistance in Human Colorectal Cancer - Li, Guangcai; Li, Wenwen; Dai, Hongsheng; He, Xialian; Shi, Lihong; Zhang, Xiaoqian (Turkish Journal of Gastroenterology, 2024)
Background/Aims: Peptostreptococcus anaerobius plays an important role in the development of colorectal cancer, and previous studies by our group have demonstrated that Peptostreptococcus anaerobius promotes resistance to 5-Fu chemotherapy in animal models of colorectal cancer. In this study, the effects of Peptostreptococcus anaerobius on chemotherapy resistance in colorectal cancer and its possible mechanism of action were investigated from the clinical point of view. Materials and Methods: Patients were selected according to exclusion and inclusion criteria and divided into sensitive and chemotherapy groups (n = 20/group). Fecal samples were collected from the patients. The bacterial 16S rRNA genes in the samples were sequenced and the abundance and varieties in the fecal bacteria were compared between the 2 groups. Immunohistochemistry and Western blotting were used to assess interleukin 23 levels in tumor tissues. Results: Significantly elevated abundance of Peptostreptococcus was observed in fecal samples from chemoresistant colorectal cancer patients compared to those from chemosensitive individuals. Immunohistochemistry and Western blotting results showed that chemoresistant patients had higher levels of interleukin 23 relative to chemosensitive patients and the levels were positively associated with Peptostreptococcus. Conclusion: Peptostreptococcus may mediate the development of chemoresistant colorectal cancer by promoting the upregulation of interleukin 23. Efforts to target Peptostreptococcus thus have the potential to alter the prognosis of colorectal cancer patients. Cite this article as: Li G, Li W, Dai H, He X, Shi L, Zhang X. The impact and mechanism of action of Peptostreptococcus anaerobius on chemotherapy resistance in human colorectal cancer. Turk J Gastroenterol. 2024;35(10):763-771.